The P.A. Sabouroff Collection of Ancient Terracottas from The State Hermitage Museum - Elena Khodza (Les Carnets de l’ACoSt)
The Sabouroff collection was formed in Greece by Pyotr A. Sabouroff (1835–1918), Russian diplomat and statesman, between 1870 and 1879, after which it was purchased by the Imperial Hermitage in 1884. This new and updated catalogue of the Sabouroff collection includes a reconstruction of the events accompanying the purchase of this collection based on documents in the Archives of The State Hermitage Museum. In addition, detailed reports of modern methods of analyses are taken into account that have been utilized for a complete reassessment of the Sabouroff collection for its full publication.